DEVELOPMENT OF THE MASTER ULIL ALBAB MATHEMATICS LEARNING MODEL BASED ON SPIRITUAL, THEORETICAL, AND APPLICATIVE DIMENSIONS - Aniqotizzahro, Salma; Abadiyah, Sa'diyatul; Maulidiyah, Faizzatul; Fathani, Abdul Halim (Universitas Tanjungpura, 2026)
Islamic boarding schools (pesantren) as educational institutions based on spiritual values face challenges in learning mathematics, which is often perceived as difficult by students. This study aims to develop and implement the MASTER Ulil Albab mathematics learning model, an extension of the MASTER model that explicitly integrates three dimensions (spiritual, theoretical, and applicative) of Ulil Albab concept to contextualize mathematics learning within Islamic values. The research employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate). The study was conducted at MTs Ahmad Yani, Jabung, Malang Regency, involving 27 eighth-grade students (n = 27). This research uses the Research and Development (R&D) method with a 4D approach (Define, Design, Develop, Disseminate) to produce a valid and effective learning model. Data were collected using a needs analysis questionnaire and a posttest, and analyzed using descriptive quantitative techniques. The results of the needs analysis indicate that students require an integrative mathematics learning model. Furthermore, the posttest results show an average score of 87.59, exceeding the Minimum Completeness Criteria (KKM). These findings provide an indication of improved students’ understanding of mathematics after the implementation of the MASTER Ulil Albab model. This study highlights the novelty of integrating the MASTER learning syntax with the Ulil Albab concept, emphasizing the balance of spiritual awareness, theoretical understanding, and applicative skills in mathematics learning.